Pengaruh Strategi Pemasaran dan Kualitas Pelayanan Terhadap Keputusan Pembelian pada Toko Zulaikha Bika Ambon Medan - Kartika, Adelya; Sabrina, Hesti; Prayudi, Ahmad (Mahesa Research Center, 2025)
This research examines the influence of Marketing Strategy and Service Quality on Purchasing Decisions at the Zulaikha Bika Ambon Shop in Medan. This research uses a quantitative approach, which is measured using a multiple linear regression-based method with the SPSS 21 program. Data collection is through distributing questionnaires. The population of this research is all consumers of the Zulaikha Bika Ambon Medan Shop located at the Jl. Mojopahit branch no 07 A-c Medan with a research sample of 99 respondents. The sampling technique uses a random sampling method. Data analysis techniques are carried out using instrument tests, classical assumption tests, statistical tests and hypothesis tests. Based on the research results, it show that (1) Marketing Strategy has a positive effect on purchasing decisions at the Zulaikha Bika Ambon Shop in Medan., (2) Service Quality has a positive effect on Purchasing Decisions at the Zulaikha Bika Ambon Shop in Medan., (3) Marketing Strategy and Service Quality as a whole. Simultaneously has a positive effect on satisfaction with purchasing decisions at the Zulaikha Bika Ambon Shop in Medan.